The survival and growth performance of juvenile cardinal tetra (Paracheirodon axelrodi) with application of tropical almond (Terminalia catappa) leaves - NURHIDAYAT NURHIDAYAT; LIZA WARDIN; EDIYANTO SITORUS (Smujo International, 2016)
Abstract. Nurhidayat, Wardin L, Sitorus E. 2016. The survival and growth performance of juvenile cardinal tetra(Paracheirodon axelrodi) with application of tropical almond (Terminalia catappa) leaves. Nusantara Bioscience 8: 1-4. The proportional appearance of the length and the weight, and the color pattern are key factors of ornamental fishes. Modification of environment and application of food may be done to increase fish quality. The addition of active compound of tropical almond (Terminalia catappa) leaves at certain doses can be done to increase survival rate and the growth of juvenile cardinal tetra (Paracheirodon axelrodi). This research used completely randomized design with four treatments and four replications. Therefore, there were 16 experimental units. The treatments were four doses of almond leaves: D0 (without almond leaves), D1 (0.5 g/L), D2 (1.5 g/L) and D3 (2,5 g/L). Experimental fish used in this research was cardinal tetra. The result showed that 0.5 g/L and 1.5 g/L of almond leaves addition resulted in 100% survival rate. Those concentrations also increased the body length by 1.28 cm and increased the weight by 0.092 g. The best water parameters used during the research were: temperature of 25-29oC, dissolved oxygen of 6-6.6 ppm, pH of 6-6.5, alkalinity of 22.66-33.98 ppm, water hardness of 26.17-57.00 ppm, ammonia of 0.0052-0.0104 ppm, and nitrite of 0.0029-0.0696 ppm.